First record of Andinia panica (Orchidaceae) from Colombia - Kolanowska, Marta; Trejo, Ramiro Medina; Szlachetko, Dariusz L. (Biodiversity: Research and Conservation, 2018)
Andinia panica, previously known exclusively from the type locality in Ecuador, is reported for the first time from Colombia. Characteristic of population found in Valle de Sibundoy is provided together with photographs of the specimen and information about its habitat. Moreover, the comparative morphology of species included in Andinia subgenus Minuscula, is presented together with the key to species identification.